2013
DOI: 10.3109/13625187.2013.856405
|View full text |Cite
|
Sign up to set email alerts
|

Can uterine artery Doppler parameters predict copper intrauterine device-induced side effects?

Abstract: OBJECTIVES To evaluate the predictive value of uterine artery Doppler characteristics in predicting copper intrauterine device (IUD)-induced side effects such as dysmenorrhoea and menorrhagia, and worsening of dyspareunia. METHODS One hundred and twenty regularly menstruating women were enrolled in the study. All underwent transvaginal uterine artery Doppler analysis in the early follicular phase, on two occasions: before insertion of the IUD, and six months after insertion. Pre- and post-insertion resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…Indeed, there is some controversy regarding uterine artery PI and RI in IUCD users. Some studies suggest no difference in RI and PI before and after insertion [10][11][12][13], and others demonstrate a PI increase in the midluteal phase, yet still agreed with this study and suggested decreased uterine artery PI after IUCD insertion [14]. Some studies reported no statistical difference between women with IUCD-induced heavy menstrual bleeding and those using IUCD with normal menstruation [15,16].…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, there is some controversy regarding uterine artery PI and RI in IUCD users. Some studies suggest no difference in RI and PI before and after insertion [10][11][12][13], and others demonstrate a PI increase in the midluteal phase, yet still agreed with this study and suggested decreased uterine artery PI after IUCD insertion [14]. Some studies reported no statistical difference between women with IUCD-induced heavy menstrual bleeding and those using IUCD with normal menstruation [15,16].…”
Section: Discussionsupporting
confidence: 75%
“…They found no significant difference concerning uterine artery RI and PI values before and after IUD insertion. Mutlu et al 17 compared the uterine artery PI and RI values of 104 women before copper IUD insertion and 6 months later. They observed no significant change in uterine artery PI and RI values.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these findings, Yigit et al 18 reported higher uterine artery PI and S/D values 3 to 5 months after the insertion of copper IUD than before insertion. All the above‐mentioned studies 11,16‐18 compared the results of patients using IUD for less than a year. In accordance with the aforementioned studies, 11,16‐18 we observed that uterine artery Doppler variables in women having used IUDs for less than 1 year were similar to those who did not use an IUD.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic pain was the most frequently IUD associated complication; it was defined as having significant pain and cramping during and / or prior to menstrual cycle that were not present before IUD was inserted (6). This cramping (menstrual pain) is thought to be due to the presence of increased abnormal uterine contractility and decreased uterine blood flow (7). It was found that according to the analysis of Demographic and Health Survey (DHS) data 38% of women had chosen to discontinue the use of IUD due to its complication as bleeding and pelvic pain (8).…”
Section: Introductionmentioning
confidence: 99%
“…Copper IUDs were recorded to increase the release of prostaglandin and even to cause pain. This pain is one of the cited reasons for cessation of intrauterine contraception or a reason for not using the IUD (3), (7) & (9). Even though these side effects, the cumulative continuation rates for IUDs up to three years have been reported to be among the highest of all modern methods of contraception (10) & (11).…”
Section: Introductionmentioning
confidence: 99%